ANALISIS MODEL PROBABILISTIK PUNAHNYA MUTAN PARASIT MALARIA YANG RESISTEN TERHADAP KLOROKUIN PLUS AMODIAKUIN - Jonner Nainggolan (INTEGRAL, 2013)
In this paper probabilistic models are developed from a model of malaria parasite population dynamics proposed by Macdonald [1] based on Galton-Watson branching and generating Negative Binomial distribution with maximum likelihood estimation, to test a model of malaria parasite extinction. Values of the model parameters are calculated using a samples of patients treated at the Jayapura General Hospital. The response of malaria parasites to chloroquine plus amodiaquine was examined with in- vivo tests. Samples were taken from 40 people, with 17 sensitive samples, 9 samples of degree of RI, 8 samples of degree of RII, and 6 samples of degree RIII. The data sample used in the model must satisfy the Negative Binomial distribution. Model construction approach includes: the basic model, study models, and mathematical calculations. A goodness of fit test was used to test the feasibility of the model. The model was focused on predicting the probability of the extinction of mutant malaria parasites resistant to chloroquine plus amodiaquine in a local population. Data analysis revealed the point of the probability of the extinction of resistant malaria parasites using Galton-Watson theorem is s = 0.8814. The probability of the extinction of malaria parasites resistant to chloroquine plus amodiaquine is φNB =0,8902.Keywords: Probabilistic model, malaria, the point of the extinction of parasites,chloroquine plus amodiaquine.Model probabilistik dalam tulisan ini merupakan pengembangan model dinamika populasi parasit malaria yang dikaji oleh Macdonald [1] berbasiskan pencabangan Galton-Watson dan pembangkit distribusi Binomial Negatif dengan estimasi mak- simum likelihood. Kombinasi model pencabangan Galton-Watson dan pembangkit distribusi Binomial Negatif digunakan untuk mengkaji model peluang punahnya parasit malaria. Untuk menentukan nilai parameter-parameter model digunakan data pasien yang berobat di Rumah Sakit Umum Jayapura. Untuk melihat respon parasit malaria terhadap obat antimalaria, digunakan tes in-vivo. Jumlah sampel dalam penelitian ini sebanyak 40 orang, 17 sampel sensitif, 9 sampel derajat RI, 8 sampel derajat RII, dan 6 sampel derajat RIII. Data sampel yang digunakan pada kajian model harus memenuhi syarat distribusi Binomial Negatif. Kemudian dilakukan pengujian kelayakan model dengan menggunakan goodness of fit test. Kajian model tersebut difokuskan untuk memprediksi besarnya probabilitas punah- nya mutan parasit malaria yang resisten terhadap klorokuin plus amodiakuin. Dari hasil analisis data diperoleh titik punahnya parasit malaria dengan menggunakan teorema Galton-Watson s = 0,8814. Sedangkan peluang punahnya parasit malaria yang resisten terhadap klorokuin plus amodiakuin adalah φN B = 0, 8902.Kata Kunci: Model probabilistik, malaria, titik punahnya parasit, klorokuin plusamodiakuin.